COMPUTER PROGRAMS FOR THE COMPARISON BETWEEN CORRELATIONS: INDEPENDENT SAMPLES - Silver, N. Clayton (2016)
There is a variety of techniques to test the differences between independent correlations which are not available in statistical programs familiar to the researcher. We present examples of these techniques to evaluate different hypotheses within the context of correlations in independent samples, together with interactive, friendly and freeware computer programs.